Optimal VAsopressor TitraTION in patients 65 years and older (OVATION-65): protocol and statistical analysis plan for a randomised clinical trial. Issue 11 (14th November 2020) - Masse, Marie-Hélène; Battista, Marie-Claude; Wilcox, Mary Elizabeth; Pinto, Ruxandra; Marinoff, Nicole; D'Aragon, Frédérick; St-Arnaud, Charles; Mayette, Michael; Leclair, Marc-André; Quiroz Martinez, Hector; Grondin-Beaudoin, Brian; Poulin, Yannick; et al.
Abstract : Introduction: Vasodilatory hypotension is common among intensive care unit (ICU) patients; vasopressors are considered standard of care. However, optimal mean arterial pressure (MAP) targets for vasopressor titration are unknown. The objective of the Optimal VAsopressor TitraTION in patients 65 years and older (OVATION-65) trial is to ascertain the effect of permissive hypotension (vasopressor titration to achieve MAP 60–65 mm Hg) versus usual care on biomarkers of organ injury in hypotensive patients aged ≥65 years. Methods and analysis: OVATION-65 is an allocation-concealed randomised trial in 7 Canadian hospitals. Eligible patients are ≥65 years of age, in an ICU with vasodilatory hypotension, receiving vasopressors for ≤12 hours to maintain MAP ≥65 mm Hg during or after adequate fluid resuscitation, and expected to receive vasopressors for ≥6 additional hours. Patients are excluded for any of the following: active treatment for spinal cord or acute brain injury; vasopressors given solely for bleeding, ventricular failure or postcardiopulmonary bypass vasoplegia; withdrawal of life-sustaining treatments expected within 48 hours; death perceived as imminent; previous enrolment in OVATION-65; organ transplant within the last year; receiving extracorporeal life support or lack of physician equipoise. Patients are randomised to permissive hypotension versus usual care for up to 28 days. The primary outcome is high-sensitivity troponin T, a biomarker of cardiac injury, on day 3. Secondary outcomes include biomarkers of injury to other organs (brain, liver, intestine, skeletal muscle); lactate (a biomarker of global tissue dysoxia); resource utilisation; adverse events; mortality (90 days and 6 months) and cognitive function (6 months). Assessors of biomarkers, mortality and cognitive function are blinded to allocation. Ethics and dissemination: This protocol has been approved at all sites. Consent is obtained from the eligible patient, the substitute decision-maker if the patient is incapable, or in a deferred fashion where permitted. End-of-grant dissemination plans include presentations, publications and social media platforms and discussion forums. Trial registration number: NCT03431181 .